Acute effects of brewed cocoa consumption on attention, motivation to perform cognitive work and feelings of anxiety, energy and fatigue: a randomized, placebo-controlled crossover experiment. Issue 1 (December 2017) - Boolani, Ali; Lindheimer, Jacob; Loy, Bryan; Crozier, Stephen; O'Connor, Patrick
Abstract Background Acute effects of caffeinated and non-caffeinated cocoa on mood, motivation, and cognitive function are not well characterized. The current study examined the acute influence of brewed cocoa, alone and with supplemental caffeine, on attention, motivation to perform cognitive tasks and energy and fatigue mood states. Methods A randomized, double-blinded, within-subjects crossover trial was conducted with four 473-milliliter brewed beverage treatments: cocoa, caffeinated cocoa (70 milligrams caffeine total), placebo (flavored and colored brewed water) and positive control (placebo plus 66 milligrams caffeine, "caffeine alone"). Participants (n  = 24) were low consumers of polyphenols without elevated feelings of energy. Before and three times after beverage consumption, a 26-minute battery was used to assess motivation to perform cognitive tasks, mood and attention (serial subtractions of 3 and 7, the continuous performance task, and the Bakan dual task) with a 10-minute break between each post-consumption battery. The procedure was repeated with each beverage for each participant at least 48 h apart and ±30 min the same time of day. Data were evaluated using Treatment X Time analysis of covariance controlling for hours of prior night's sleep. Results Compared to placebo, cocoa reduced overall false alarm errors progressively across time with 0.92, 1.44 and 2.35 fewer false alarms on average 22–48, 60–86 and 98–124 min post-consumption (η 2  = 0.08, p  = 0.019). Caffeinated cocoa: (i) attenuated the anxiety-provoking effects of cognitive testing found after drinking caffeine alone (η 2  = 0.064, p  = 0.038), and (ii) increased accuracy (η 2  = 0.085, p  = 0.01) and reduced omission errors (η 2  = 0.077, p  = 0.016) on the Bakan primary task compared to cocoa alone. Conclusions Brewed cocoa can acutely reduce errors associated with attention in the absence of changes in either perceived motivation to perform cognitive tasks or feelings of energy and fatigue. Supplemental caffeine in brewed cocoa can enhance aspects of attention while brewed cocoa can attenuate the anxiety-provoking effects found from drinking caffeine alone. Trial registration ClinicalTrials.gov Identifier:NCT01651793 . Registered July 25, 2012.